Study on vibrational Raman modes and electric properties of lead-free sodium bismuth titanate – bismuth magnesium zirconate piezoelectric ceramics - D.E. Jain Ruth (Chemical Physics Impact, 2023)
Raman spectra of lead- free piezoelectric sodium bismuth titanate-bismuth magnesium zirconate (1-x)(Na0.5Bi0.5)TiO3-xBi(Mg0.5Zr0.5)O3 [NBT-BMZ] ceramics are recorded and analyzed. Vibration phonon frequencies associated to Bi-O, Na-O, TiO6 octahedra and oxygen vibrations are noticed. Intensity changes on E(TO1) mode at 110 cm−1 arising from Bi-O vibrations is due to difference in polarizability of substituted cations in the A-site of NBT. Frequency shift in 247 and 281 cm−1 mode are attributed to lattice change and TiO6 octahedral rotation induced by substitution of BMZ in NBT. Increase of E(TO4) and A1(TO4) vibration modes due to decrease of TiO6 octahedral rotation reduces the lattice distortion and homogeneous strain which in turn prompts softening of coercive field and enhances remnant polarization as well as dielectric constant in NBT-BMZ piezoceramics. Also, vibrational Raman modes E(TO1), E(TO4) and A1(TO4) are the decisive phonons for interpreting the interesting dielectric behavior of NBT-based ceramics.